Effect of Daily Iron Supplementation on Infantile Iron Homeostasis in Preterm Infants - Li, Mingyan; Lv, Ying; Ying, Jionghuan; Xu, Lin; Chen, Weijun; Zheng, Quan; Ji, Chai; Shao, Jie (Frontiers in Pediatrics, 2021)
Objective：The aim of this study was to investigate the effects of unified iron supplementation and identify the factors related to the iron homeostasis among preterm infants. Method：A total of 250 preterm infants were divided into neonatal anemic (NA, n=154) and non-neonatal anemic group (NNA, n=96). Iron supplements at a dose of 2mg/kg per day were given from 40 weeks’ gestational age to 6 months. Iron status parameters were measured at 3 and 6 months respectively. Prevalence of iron deficiency (ID) and iron deficiency anemia (IDA), and the correlated factors were analyzed. Growth and side-effects were monitored. Results：There were no significant differences for the prevalence of ID or IDA between the two groups. Multivariate regression analyses showed that higher Hb at birth and early treatment of blood transfusion reduced the risk of ID/IDA at 3 months (all p<0.05); while higher level of Hb at 3 months(p=0.004) and formula feeding reduced the occurrence of ID/IDA at 6 months (p<0.05); males had a 3.35 times higher risk to develop ID/IDA than girls (p=0.021). No differences in growth and side effects were found. Conclusion：A daily dose of 2 mg/kg iron supplement is beneficial to maintain iron homeostasis in majority preterm infants within 6 months regardless of their neonatal anemia history. Under the routine iron supplementation, Hb level at birth and at 3 months, early treatment of blood transfusion, gender and feeding patterns are the major factors affecting the prevalence of ID/IDA among preterm infants in infancy.